A Nonsynonymous Single-nucleotide Polymorphism in SLC24A5 Regulates Feather Pigment Deposition in Chinese Yellow Quail - Xiaohui Zhang; Fanghu Wu; Yanxia Qi; Yuanyuan Shang; Lingyun Fan; Yifei Wang (The Journal of Poultry Science)
Plumage color in birds is determined by melanin, whose synthesis and transport are affected by many genes, including specific solute carriers (SLCs). The main objective of this study was to detect polymorphisms in the SLC24A5 gene of the Chinese yellow quail (Coturnix japonica) and analyze their effect on tyrosinase activity in skin tissue and melanin content in down feathers. The cDNA of the SLC24A5 gene was cloned by RT-PCR and subjected to Sanger sequencing. Potential single-nucleotide polymorphisms (SNPs) were screened using multiple sequence alignment. The screened nonsynonymous SNPs were genotyped across 265 Chinese yellow quails using the kompetitive allele-specific PCR method. The association of genotypes with tyrosinase activity in the skin and melanin content in down feathers was analyzed. The g.8884145A/G SNP was identified in exon 9 of the SLC24A5 gene, resulting in an Asp396Ala mutation. The mutant residue was predicted to be located inside the eighth transmembrane helix of the SLC24A5 protein, which is primarily responsible for recognizing Na+/Ca2+ ions. Mutant individuals had significantly lower total melanin content in the feathers and tyrosinase activity in dorsal skin, in spite of no significant difference in SLC24A5 mRNA expression in the same tissues. This study indicates that the g.8884145A/G mutation reduced tyrosinase activity by affecting the function of the SLC24A5 protein, which in turn decreased melanin content of down feathers in Chinese yellow quail.